2001
DOI: 10.1148/radiology.219.2.r01ma42427
|View full text |Cite
|
Sign up to set email alerts
|

US Findings in the Scrotum of Extreme Mountain Bikers

Abstract: US shows a significantly higher prevalence of extratesticular and testicular disorders in these mountain bikers compared with nonbikers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 22 publications
2
46
1
3
Order By: Relevance
“…Punctate epididymal calcification has been described in patients on maintenance hemodialysis, 3 and focal epididymal macrocalcification after chronic repeated microtrauma has been seen in extreme mountain bikers. 4 The foci of epididymal calcification in our case would be entirely consistent with microlithiasis on sonographic criteria, as described in the testis, and appear quite distinct from other previously described causes of epididymal calcification.…”
Section: Discussionsupporting
confidence: 89%
“…Punctate epididymal calcification has been described in patients on maintenance hemodialysis, 3 and focal epididymal macrocalcification after chronic repeated microtrauma has been seen in extreme mountain bikers. 4 The foci of epididymal calcification in our case would be entirely consistent with microlithiasis on sonographic criteria, as described in the testis, and appear quite distinct from other previously described causes of epididymal calcification.…”
Section: Discussionsupporting
confidence: 89%
“…Frauscher et al (6) and Artas and Orhan (1) found the mean diameters of scrotal calculi to be 4±3 mm (range, 2-14 mm) and 4.22±2.42 mm (range, 2-10 mm), respectively. In our study, we found the mean size of the scrotal calculi to be 3.7±1.4 mm (range, 1.6-7.0 mm), which is similar to the sizes reported previously.…”
Section: Discussionmentioning
confidence: 98%
“…However, repeated chronic microtrauma to the scrotum may be a risk factor for the development of calculi. Frauscher et al (6) and Turgut et al (7) reported the existence of scrotal calculi in 81% of extreme mountain bikers and 7% of equestrians, respectively. In our study, the frequency of scrotal calculi was 1.95% from a total of 3435 men who had been consecutively recruited from the surgical and internal medicine clinics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Frauscher and colleagues, performing ultrasound testing, reports that mountain bikers show greater incidence of scrotal and testicular abnormalities as compared to non-bikers [108]. Among the observed abnormalities, some should be highlighted: testicular calcifications, hidrocele, varicocele, and testicular microlithiasis.…”
Section: Exercise and Testicular Microtraumamentioning
confidence: 98%